Chrysin Protects Rat Kidney from Paracetamol-Induced Oxidative Stress, Inflammation, Apoptosis, and Autophagy: A Multi-Biomarker Approach - Fatih Mehmet Kandemir; Sefa Kucukler; Eyup Eldutar; Cuneyt Caglayan; İlhami Gülçin (Scientia Pharmaceutica, 2017)
Paracetamol (PC) is a safe analgesic and antipyretic drug at therapeutic doses, and it is widely used in clinics. However, at high doses, it can induce hepatotoxicity and nephrotoxicity. Chrysin (CR) is a natural flavonoid that has biological activities that include being an antioxidant, an anti-inflammatory, and an anti-cancer agent. The main objective of this study was to investigate the efficacy of CR against PC-induced nephrotoxicity in rats. CR was given orally via feeding needle to male Sprague Dawley rats as a single daily dose of 25 or 50 mg/kg for six days. PC was administered orally via feeding needle as a single dose on the sixth day. PC caused significant glutathione depletion, lipid peroxidation, increased serum toxicity markers (serum urea and creatinine), and reductions in activities of antioxidant enzymes (superoxide dismutase — SOD, catalase — CAT, and glutathione peroxidase — GPx). The renal protective effect of CR was associated with decreasing the regulation of serum renal toxicity markers and increasing the regulation of antioxidant enzyme activities. Additionally, PC led to significant increases in the levels of inflammatory markers including tumour necrosis factor-alpha (TNF-α), interleukin-1β (IL-1β) and interleukin-33 (IL-33). Furthermore, PC induced apoptotic tissue damage by increasing cysteine aspartate-specific protease-3 (caspase-3) activity and autophagic tissue damage by increasing the expression of light chain 3B (LC3B). CR therapy significantly decreased these values in rats. This study demonstrated that CR has antioxidant, anti-apoptotic, anti-inflammatory and anti-autophagic effects on PC-induced kidney toxicity in rats.